The Relationship Between Motivation for Physical Activity, Physical Activity Level, and Body Mass Index for University Students - Alecu Stefan; Onea Gheorghe Adrian; Badau Dana (My University, 2025)
The object of the study was to identify the relationship between the motivation for physical activity, the physical activity index (PAI), and the body mass index (BMI) for a sample of university students, taking into consideration the gender difference. The study subjects were 813 (340 men and 473 women), and the age range of the participants varied between 18 and 25 years. The RM 4-FM (Motivation for Physical Activity and Exercise) and PAI online questionnaires were applied to measure the motivation and the physical activity level. The study’s novelty focused on analyzing how intrinsic and extrinsic motivation interact and correlate BMI and physical activity levels (PAI). Regarding gender, we approached the identification of motivational differences and the level of physical activity of students from non-sports faculties to identify relevant aspects for promoting proactive behaviors. Results revealed significant gender differences: men had a higher PAI (53.48 ± 28.11) than women (36.67 ± 23.92, p < 0.01); BMI (23.25 vs. 21.69, p < 0.01). The Cohen’s value of RAI of RM 4-FM, BMI, and PAI were > 0.5, indicating a large effect size. The analysis presents a unique perspective of the interactions between psychological factors, motivation, and physical characteristics, providing insight into developing strategies to improve and promote a proactive lifestyle.
Keywords: physical activity; intrinsic and external motivation; BMI; health behavior; proactive behavior